Hot Topics in Infection and Immunity in Children III - Pollard, Andrew J.; Finn, Adam.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2006)
This book is based on the course “Infection and Immunity in Children 2005” which was held at St Catherine’s College Oxford, UK in June 2005. This is the third book in this series covering topics in infection and immunity during childhood and based on the Oxford courses. These courses, and their companion books, are aimed at encouraging excellence in clinical practice and raising the pro? le of paediatric infectious disease with a particular eye on the needs of trainees in the specialty. At the time of writing a fourth course is already at an advanced stage of planning for June 2006 with a completely new programme once again. You will ? nd in this book a wealth of state of the art information about various aspects of paediatric infectious diseases written by leading authorities in the ? eld. We hope this volume will bring new insights into the management of children with infectious diseases and improve the health of children. Andrew J Pollard and Adam Finn January 2006 v Acknowledgments We are indebted to all of the contributors to this text who have generously provided their carefully written manuscripts in good time for editing and publication. We are also grateful to the staff of St Catherine’s College, Oxford, UK who hosted Infection and Immunity in Children 2005 on which the text is based.
Warfare and the State of the World’s Children -- How Do We Treat Children with Severe Malaria? -- The Neglected Tropical Diseases: The Ancient Afflictions of Stigma and Poverty and the Prospects for their Control and Elimination -- Viral Haemorrhagic Fevers Caused by Lassa, Ebola and Marburg Viruses -- Rotavirus and Rotavirus Vaccines -- Transient Deficiencies of T-Cell-Mediated Immunity in the Neonate -- Controversies in Neonatal Sepsis: Immunomodulation in the Treatment and Prevention of Neonatal Sepsis -- Chlamydia trachomatis Genital Infection in Adolescents and Young Adults -- The Role of Inflammation and Infection in the Development of Chronic Lung Disease of Prematurity -- Streptococcus pneumoniae: Infection, Inflammation and Disease -- Impact of Antimicrobial Resistance on Therapy of Bacterial Pneumonia in Children -- Diagnosis and Prevention of Pneumococcal Disease -- New Antibiotics for Gram-Positive Infections -- Clinical Manifestations of Nontuberculous Mycobacteria -- Kingella kingae: An Emerging Pediatric Pathogen -- How to Treat Acute Musculoskeletal Infections in Children -- Prevention of Transmission of HIV-1 from Mothers to Infants in Africa -- Practical Aspects of Antiretroviral Treatment in Children -- Antibiotic Treatment for Acute Otitis Media in Children -- Antibiotic Prophylaxis for the Prevention of Recurrent Urinary Tract Infections in Children -- Human Metapneumovirus: An Important Cause of Acute Respiratory Illness.
Keywords: Immunology; Infectious diseases; Pediatrics; Virology; Microbiology; Immunology; Infectious Diseases; Pediatrics; Virology; Microbiology